Analysis of Indonesian Corn’s Competitiveness In International Trade - Wanto, Hary (LifeSciFi, 2021)
Indonesia is an agricultural country that is blessed with abundant natural resources, both biological and non-biological natural resources. Various natural products grow abundantly in Indonesia, including food crops. Understanding the relationship between exports and competitiveness can provide a more holistic view regarding the position of Indonesian corn in international competition. the ability of a commodity to compete in foreign markets or the ability to survive in the domestic market and compete with commodities from abroad. If a product has competitiveness, the product is in great demand by many consumers. The data obtained can be in the form of numbers or aggregated qualitative data. The qualitative approach provides the flexibility to gain an in-depth understanding of the phenomenon under study, while quantitative data allows for mathematical measurement and analysis, Ministry of Finance, World Bank, Agricultural Service, and other published sources. As a result of quantitative analysis calculations, conclusions can be obtained from the research carried out. Indonesian corn production has a positive and significant effect on the competitiveness of Indonesian corn.